Lubricating effect of oils by controlling the concentration of chemical components of the additives - Milanenko, O.A.; Bobro, A.M. (Problems of Tribology, 2026)
A proposed and substantiated multifactorial approach to assessing the lubricating effect of oils, considering the influence of physicochemical factors and rheological characteristics on the evolution of the creation and adaptation of chemically modified boundary layers (CMBLs) to real operating conditions in conditions of the partial EHD lubrication mode. Comparing the results of the anti-wear and anti-friction properties of the studied oil samples, while complying with the additive manufacturer's conditions for the mass fraction of sulfur, which is 1.488–1.9662%, a necessary condition for the best results in terms of the combined action of the anti-wear and anti-friction properties of the oils is to establish a total additive concentration of 3.9–4.9% with a phosphorus mass fraction of 0.046–0.057%. In the series of samples studied, sample 4 with a concentration of 4.9% additive shows the best universal properties, especially for the operation of units with combined engine and transmission systems (universal STOU oils for agricultural machinery).